New and old regulations: An analysis of coexistence regulations in secondary school. - Litichever, Lucía; Machado, Luciano; Núnez, Pedro; Roldán, Soledad; Stagno, Leandro (Última Década, 2020)
This project is carried out within the framework for the investigation «Intersections between inequality and secondary education: an analysis of the dynamics of production and the reproduction of scholastic and social inequality in four jurisdictions». We carried out a comparison of the Regulations of Coexistence of the secondary schools of the jurisdictions of Plata and Neuquén. From the compiled documentation and the interviews carried out with the students regarding scholastic rules, it is of interest to us to analyze the ways which traditionally regulate the modern school, especially where appearance and punctuality persist or are redefined at present. At the same time, we will investigate new transgressions anticipated by the rules. In connection with the hypotheses of the project, we will maintain the presence of forms to structure the coexistence in the schools, dissimilar by jurisdictions and the social sectors taking into account the configuration and reconfiguration of inequality.